Sine-Function Method In The Soliton Solution Of Nonlinear Partial Differential Equations - Rab, M Abdur; Akhter, Jasmin (GANIT: Journal of Bangladesh Mathematical Society, 2013)
In this paper we establish a traveling wave solution for nonlinear partial differential equations using sine-function method. The method is used to obtain the exact solutions for three different types of nonlinear partial differential equations like general equal width wave equation (GEWE), general regularized long wave equation (GRLW), general Korteweg-de Vries equation(GKDV) which are the important soliton equations DOI: http://dx.doi.org/10.3329/ganit.v32i0.13647 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 32 (2012) 55-60